Multifocal osteonecrosis as a consequence of a new coronavirus infection - A. A. Klimenko; N. A. Demidova; D. Yu. Andryashkina; N. M. Babadayeva; A. A. Kondrashov; Yu. M. Saakyan (Научно-практическая ревматология)
The impact of the transferred coronavirus infection on the musculoskeletal system still remains an urgent problem. Аrthralgia, myalgia, arthritis, autoimmune disorders and also osteonecrosis are may be development of the postCOVID period. This article discusses the case of the debut of multifocal osteonecrosis after a coronavirus infection.